Relevant Factors of Innovative Activities of Small Business in Regions - Vaysman, Yelena Davidovna; Podshivalova, Mariya Vladimirovna (Economy of Regions, 2015)
The article discusses the system analysis aimed to identify the key reasons for the low innovation activity in the regions of the Russian Federation. The research is based on the hypothesis according to which the holism and systematic principles need to be applied for analyzing the reasons of the low innovative activity of small business in the regions,. To implement these principles, the authors have used the concept of «minimum number of descriptive levels of socio-economic system». In the research, the spiritual and cultural, cognitive, institutional, material and technological «layers» of the socio-economic system are investigated. The particular attention is paid to the cognitive and institutional segments. The methodological basis of the research is the methods of correlation and regression analysis, maps of positioning, integrated assessment, the authors method of assessing the development of the knowledge-based economy and clustering. The quality of innovative small firms’ institutional environment is assessed using the resource approach. The authors have obtained the following results. The rate of demand growth for knowledge in the regions exceeded the growth rate of the regional offers of knowledge, including the innovative development of small businesses. A delayed reaction of the suppliers of innovative ideas to the corresponding demand is showed. The trend of differentiation increase of the Russian regions in terms of the knowledge-based economy’s development is revealed. A significant linear correlation of small firms’ innovative activities and the quality of institutional environment haven’t been discovered. It is shown that the regions are almost similar in the quality of basic socio-economic institutions, and more than 60 % of the regions have the intensity of small businesses’ innovation processes below the national average level. The obtained results allow to expand the scientific and methodological basis to stimulate the innovative activity of small business both at the macro and meso-level. The authors have concluded that since all the selected layers of socio-economic systems are interconnected and in each of them there are a number of «bottlenecks», the active smart measures undertaken by the State for the innovation infrastructure development can not lead to the increase in the small business innovative activity.